Nanoemulsion of Sideroxylon obtusifolium as an Alternative to Combat Schistosomiasis - Rangel, Leonardo da Silva; Passos de Oliveira, Adriana; Falcão, Deborah Quintanilha; Santos, Marcelo Guerra; Von Ranke, Natalia Lindimar; Rodrigues, Carlos Rangel; Santos, José Augusto Albuquerque dos; Rocha, Leandro; Faria, Robson Xavier (Frontiers in Plant Science, 2022)
Schistosomiasis is caused by the intestinal parasite Schistosoma mansoni. Individuals are affected by schistosomiasis when they are exposed to aquatic environments contaminated with Schistosoma cercariae that emerged from the infected intermediate host mollusk of the genus Biomphalaria. The WHO recommends using molluscicidal products to reduce the snail population and disease transmission. The WHO encourages the search for alternative substances in schistosomiasis control. Natural products are seen as a promising alternative because they are abundant in countries where schistosomiasis is endemic and have many different substances in their extracts, impairing cases of resistance. Therefore, the nanoemulsion effect of a butanol-soluble fraction of Sideroxylon obtusifolium leaves was evaluated against three study points in the biological cycle of the disease, that is, adults and young Biomphalaria glabrata, spawning by the host mollusk, and infectious larvae of the parasite. Extract-SOB (butanol fraction) and nano-SOB (nanoemulsion) demonstrated promising activity in adult B. glabrata population control with an LC50 of 125.4 mg/L, an LC90 of 178.1 mg/L, an LC50 of 75.2 mg/L, and an LC90 of 97 mg/L. Nano-SOB presented greater potency against young B. glabrata, with an LC90 of 72.1 mg/L and an LC50 of 58.3 mg/L. Still, relevant activity against S. mansoni cercariae was eliminated in 4 h (LC90: 34.6 mg/L). Nano-SOB reduced viable spawning by approximately 30% at 178.1 and 97 mg/L. Referring to most substances in this extract, quercetin-3-rhamnosyl-(1-6)-galactoside and hyperoside may cause low environmental toxicity and human toxicity according to in silico analysis. Thus, nano-SOB is a promising agent to combat B. glabrata population growth and schistosomiasis transmission.